Estrategias lúdicas para desarrollar la psicomotricidad fina en niños de Segundo Grado de Educación General Básica de la Unidad Educativa "Simón Rodríguez " del cantón Riobamba, año lectivo 2022-2023. - Toapanta Chiliguana, Gabriela del Rocio (2023)
In the "Simón Rodríguez" Educational Unit, the importance of using recreational strategies to develop children's fine motor skills was evident, which by not taking into account the shortcomings that children present at initial levels could harm them later in activities that involve Precise movements such as cutting, coloring, shaping and gluing, being skills that must be learned correctly for the subsequent writing process, teachers by not innovating playful strategies with children do not generate motivation or enjoyment for learning, developing a classroom environment monotonous, without interaction between teacher and student. For this, as a first point, it was recognized what types of play strategies teachers use with their students. Subsequently, the student's level of fine psychomotor development was classified. Finally, five play strategies that help the development of fine psychomotor skills in the students were stated children’s teachers can use. This methodologically developed research was based on previous work and scientific articles on playful strategies and fine psychomotor skills in children. It had a mixed approach. Its design is non-experimental; it was a bibliographic and field research at a descriptive level. The sample was of a non-probabilistic type since it was taken at the researcher's discretion and was applied to twenty students and two teachers in the second year of EGB. Two techniques and instruments were used to collect data: a structured observation sheet with ten items to observe in the children and an open interview with six questions through an interview guide for teachers. The results demonstrated that using playful strategies generates benefits in children's fine motor skills since, through games, children express fun and creativity, thus improving their hand-eye coordination, precision, and grip of objects.